A NEW BI-PHASED IMAGE RESTORATION - TOUMI, A.; RECHID, N.; TALEB-AHMED, A.; BENMAHAMMED, K. (Courrier du Savoir; مجلد 12 (2012): Courrier du Savoir)
In This work a new method for image restoration is proposed. This new method is constituted of two phases. The first phase which is initialization phase, from a blurred image we get a new one by the use of the search efficiency function based on Levy distribution as first cost function. In The second phase, the obtained image is introduced to PSO for local restoration where a restoration cost function is used. The results obtained were excellent.